Peran Kemajuan Decision Support System Di Eropa : Tinjauan Dan Analisis Literature (1991-2020) - Inggar Tri Agustin Mawarni; Azzan Syahrul (P3M Politeknik Negeri Banjarmasin, 2021)
Decision Support System is a tool that can help the decision maker in setting a decision. It should be emphasized that the Decision Support System is only intended to help not to make decisions. Decisions made are the responsibility of the decision maker. This study aims to examine more deeply about the decision support system (Decision support System). But this time the researchers wanted to focus more on studying in European countries. Because researchers want to know how the role of the decision support system progress in Europe in 1990 until now. The study was conducted using qualitative descriptive methods, namely using literature or literature studies. The method of data collection is done by studying literature in journals, books, magazines, or the web that is relevant to research. The data analysis technique uses an interactive model of mile and Hubermen with 4 flow stages including collecting data, trying to formulate data or data reduction, after that the data presentation and drawing conclusions. From the data, researchers found data of 50 articles that discussed the decision support system in Europe in 1990-2020. The development of a decision support system (Decision support System) in Europe has increased or decreased in each decade Keywords: Decision Support System, Europe, System.